2021
DOI: 10.3389/fcell.2021.642665
|View full text |Cite
|
Sign up to set email alerts
|

Computational Model for Membrane Transporters. Potential Implications for Cancer

Abstract: To explain the increased transport of nutrients and metabolites and to control the movement of drug molecules through the transporters to the cancer cells, it is important to understand the exact mechanism of their structure and activity, as well as their biological and physical characteristics. We propose a computational model that reproduces the functionality of membrane transporters by quantifying the flow of substrates through the cell membrane. The model identifies the force induced by conformational chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 37 publications
(30 reference statements)
1
8
0
Order By: Relevance
“…It is valid for a large range of values of ϕ, as shown in Fig. 2 where it is compared to numerical solution of the full transport equations (12,13). The theory also agrees with the Monte Carlo simulations of Ref.…”
supporting
confidence: 74%
See 2 more Smart Citations
“…It is valid for a large range of values of ϕ, as shown in Fig. 2 where it is compared to numerical solution of the full transport equations (12,13). The theory also agrees with the Monte Carlo simulations of Ref.…”
supporting
confidence: 74%
“…Classic examples include Taylor dispersion in hydrodynamic flows [10], and the decrease of dispersion due to the energy barriers created by time independent potentials [11]. In a number of systems, such as porous media [12], zeolites, and biological channels [13], the motion of tracer particles is hindered by hard (technically speaking reflecting) boundaries or obstacles. The effective trapping of the tracer in this case is of entropic origin but it again leads to a reduction of late time diffusivity [14][15][16][17][18].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[32][33][34][35][36] In many cases, however, channels can change shape due to variations in the pressure of the medium in which they are immersed, forces exerted by particles passing through them, or the existence of external sources of energy and electrochemical gradients, as in the case of ion channels and transporters where the energy supplied comes from ATP hydrolysis. 19,37,38 Transport in flickering pores may give rise to the appearance of resonances. 39,40 It has also been shown that channel deformations can cause resonances and anti-resonances that may have an impact on transport properties.…”
Section: Introductionmentioning
confidence: 99%
“…39,40 It has also been shown that channel deformations can cause resonances and anti-resonances that may have an impact on transport properties. 37,[41][42][43] The question, therefore, arises as to whether there are optimal conditions for transport in this case that take into account the fact that the canals cannot be considered isolated from the environment. This is precisely the aim of this article.…”
Section: Introductionmentioning
confidence: 99%